Evaluation of On-Road Driving in Persons with Hemianopia and Quadrantanopia - Elgin, Jennifer (2010)
OBJECTIVE: To examine the extent to which drivers with hemianopia or quadrantanopia display safe driving skills when evaluated on-road, as compared to drivers with normal visual fields. METHOD: 22 persons with hemianopia, 8 with quadrantanopia, and 30 with normal vision were evaluated for driving skills under in-traffic conditions by an experienced occupational therapist who used a set of six 5-point rating scales. RESULTS: Over 90% of drivers with normal vision drove flawlessly or had only minor errors. Although drivers with hemianopia were more likely to receive poorer ratings for all skills evaluated, 59.1% to 81.8% performed without obvious errors (depending on the skill evaluated) or had only minor errors. The skill most commonly problematic for hemianopic drivers was lane keeping (40.9% of drivers exhibiting this problem). Seven of 8 (87.5%) quadrantanopic drivers drove without obvious errors or exhibited only minor errors. CONCLUSIONS: This study on persons with hemianopia or quadrantopia with no lateral spatial neglect and MMSE scores of ≥ 24, highlights the need to individually provide them the opportunity for an on-road driving evaluation under a variety of natural traffic conditions if they are motivated to return to driving following brain injury.